LEARNING DIFFICULTIES IN COMPREHENDING VIRUS AND BACTERIA MATERIAL FOR SENIOR HIGH SCHOOLS - Firmanshah, Muhammad Imam; Jamaluddin, J.; Hadiprayitno, Gito (JPBI (Jurnal Pendidikan Biologi Indonesia), 2020)
Previous research only focuses on the difficulties and factors causing learning difficulties without any solution. This study aimed to identify learning difficulties, factors, and alternative solutions overcoming the problems of learning difficulties about viruses and bacteria. Data collection was carried out through the provision of a concept mastery test involving 195 students (8 schools) and in-depth interviews conducted by involving 37 students (4 schools) who received the lowest test scores. Data analysis was performed using a percentage formula to determine the proportion of difficulties for each competency. The results showed that students had difficulty with the highest percentage of virus material, those were the competence of analyzing the role of viruses in life (85.64%) and virus replication process (83.21%). The competence in bacterial material which has the highest percentage of difficulty (77.26%) in identify bacterial classification. The factors causing students to have difficulty learning virus and bacteria consisted of the nature of the topic (77.03%), attitudes and learning habits (60.81%), teacher?s teaching skills (37.84%), and school facilities (27.03%). Alternative solutions are: teachers reduce the content that is complex and detailed, carry out an interactive learning process (audiovisual/animation), providing more learning experiences through practical activities, and teaching through interesting ways.